Innovative Financial Mechanism to Implement Energy Efficiency Projects in Mexico - World Bank (Washington, DC, 2014)
This report provides a summary of Energy Sector Management Assistance Program (ESMAP) supported activities in Mexico focused on the creation of a pooled financing program for multiple energy efficiency projects through a single debt instrument. The report is organized as eight chapters. Chapter one provides additional details regarding the ownership, structure and operation of an special purpose entity (SPE); it discusses the flexibility of this structure and how it can serve a pool of private or public sector projects. Chapter two provides an overview of the Mexican energy sector with a focus on the electricity supply, demand and pricing. Chapter three reviews the market potential for energy efficiency investments and provides comparative data on Mexico's energy prices and costs of capital in other countries where the energy efficiency and energy services company (ESCO) market is active. Chapter four reviews the current financial market conditions in Mexico, and the restrictive nature of commercial lending. Chapter five identifies the market, institutional and financial barriers to implementation of energy efficiency and ESCO projects in Mexico with a focus on financial issues. Chapter six provides an overview of the pilot SPE structures under development for the pool financing of multiple projects. A separate SPE is being created for public and private projects. Chapter seven reviews the current status of each SPE initiative, and takes a look into the future with a discussion of next steps. Chapter eight provides a summary of lessons learned from this project, and their application to future efforts in this area.